2007
DOI: 10.1080/13825580600826454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Sex on Line Bisection: A Study of Normal Performance with Implications for Visuospatial Neglect

Abstract: Line bisection is an established clinical task used to diagnose visuospatial neglect. To date, few studies have considered the extent to which age and sex as background variables contribute to bisection performance. Both variables affect the neural substrates underlying cognitive processes and hence the behavioural performance of bisection. The purpose of this study was to examine the effects of age and sex on normal bisection performance, using three different line lengths to elucidate the influence of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 66 publications
(88 reference statements)
5
54
2
Order By: Relevance
“…Evidence of pseudoneglect on bisection tasks in older adults was also present in the study of Varnava and Halligan (2007) collapsing across gender, though line-length effects did interact with age.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Evidence of pseudoneglect on bisection tasks in older adults was also present in the study of Varnava and Halligan (2007) collapsing across gender, though line-length effects did interact with age.…”
Section: Introductionmentioning
confidence: 75%
“…Some care is thus required in interpreting this finding, though one speculative possibility might be that older young adults within a university setting may have been more efficient in utilizing an arithmetic strategy on mental number line bisection due to increasing Running Head: ADULT DEVELOPMENTAL TRAJECTORIES 22 experience of mathematics use in their studies, though further research is called for to clarify this. The trend towards right bias in visual line bisection (a non-significant association between age and reduced left bias in the older adult sample) is a somewhat equivocal result that contributes to a similarly equivocal literature where some reports indicate a decline in left bias in visual bisection (Barret et al, 2008;Chen et al, 2011) whilst some so do not (Failla et al, 2003;Varnava & Halligan, 2007;Brooks et al, 2011). We note that the present data form a non-significant trend only apparent in the older adult sample when that sample is considered on its own, and as thus have limited explanatory power.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some studies reported a rightward bias in older participants (Failla et al 2003;Fujii et al 1995); others did not find any deviational bias (Barrett and Craver-Lemley 2008; Beste et al 2006). Varnava and Halligan (2007) examined whether age and sex-related differences influenced bisection performance. Men and women were divided equally into seven age cohorts between 14 and 80 years.…”
Section: Introductionmentioning
confidence: 99%